UPAYA MENINGKATKAN LITERASI DAN NUMERASI MELALUI PROGRAM DUTA BACA PELAJAR DAN GAME EDUKASI NUMERASI BERBASIS WEBSITE DI SEKOLAH DASAR - Oliver Chelsea Sitanggang; Silvina Noviyanti (STKIP Subang, 2025)
The low level of literacy and numeracy skills among elementary school students remains a problem that requires serious attention. Literacy and numeracy are two essential foundational competencies that underpin educational success in the 21st century. Strong literacy and numeracy skills are crucial for elementary school students to support their ability to engage in education, achieve their potential, and participate fully in society. This study aims to describe efforts to improve the literacy and numeracy skills of students at SDN 13/I Muara Bulian through the implementation of the Student Reading Ambassador Program and website-based numeracy educational games. This research employed a descriptive qualitative approach involving fourth- and fifth-grade students as research subjects. Data were collected through observation, interviews, and documentation during the implementation of the educational internship program. The Student Reading Ambassador Program was carried out through the selection of students as school literacy ambassadors, followed by regular literacy training conducted every Saturday. Meanwhile, numeracy improvement was implemented through the use of website-based numeracy educational games from Ruangguru, which were conducted twice a week for fifth-grade students. The results indicate an increase in students’ reading interest, active participation in literacy activities, as well as enhanced enthusiasm and understanding of numeracy concepts through game-based learning. Therefore, the Student Reading Ambassador Program and the use of website-based numeracy educational games from Ruangguru can serve as an effective alternative strategy for improving literacy and numeracy skills among elementary school students.